Stock market development and economic growth: dubious relationship - Nagaishi, Makoto (1999)
Does the stock market play a positive role in the process of economic growth? This paper examines the controversial issue in the Indian context. The results of the investigation indicate: (i) so far as the function of domestic savings mobilisation is concerned, Indian stock market development from the 1980s onwards has not played a prominent role, (ii) if there is further deregulation of the stock market to attract more foreign portfolio inflows into India, there seems to be no way to avoid similar problems as Mexico, Korea and Thailand, such as more volatile movement of domestic stock prices and unstable BoP positions, (iii) bank credit to the commercial sector has no positive correlationship with indicators of stock market development. These findings indicate that the functional relationship between stock market development and economic growth is, at least so far, a fond hope in the Indian context. - Reproduced
Keywords: Capital market - India; Stock exchange - India; Economic growth - India; Financial markets - India; Financial markets